2014
DOI: 10.1002/ejoc.201301603
|View full text |Cite
|
Sign up to set email alerts
|

Hetero‐Wolff Rearrangement of an α‐Sulfinyl Carbene: Thermally Activated Intersystem Crossing of the Lowest Excited Triplet State of a Ground‐State Singlet Carbene

Abstract: Laser flash photolysis (λexc = 266 nm) of α‐sulfinyl diazo compound 1b results in the formation of two transient phenomena. Transient absorption A (intense, λmax = 275 nm) shows jump‐and‐growth behaviour with a growth lifetime of τ = 2 μs. Transient absorption B (weak, λmax = 415 and 540 nm) decays with a lifetime of τ = 1.8 μs, which suggests that B decays into A. On the basis of a comparison with calculated UV/Vis spectra, transient absorption B is assigned to triplet carbene 37. DFT and CCSD(T) calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…30 The reaction of thermally excited atomic carbon with thiophene, proceeding via intermediate generation of thiacyclohexa-3,5-dien-2-ylidene, was computationally studied by McKee et al 31 The photoelectron spectrum of ethoxy(methylthio)carbene has been observed by Werstiuk et al 32 Bicyclic carbene, containing both α-sulfinyl and α-ester moieties, was registered in the excited triplet state by O'Sullivan et al using nanosecond timeresolved laser flash photolysis. 33 Recently, we found that roomtemperature photolysis of 5-alkylthioethynyl-3,3-dimethyl-3Hpyrazoles led to the generation of previously unknown (4methylpent-3-en-1-ynyl)alkylthiocarbenes, which can be trapped by simple alkenes with formation of corresponding cyclopropanes. 34 This data indicates a high reactivity of these highly unsaturated carbenes, which can be used for synthetic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…30 The reaction of thermally excited atomic carbon with thiophene, proceeding via intermediate generation of thiacyclohexa-3,5-dien-2-ylidene, was computationally studied by McKee et al 31 The photoelectron spectrum of ethoxy(methylthio)carbene has been observed by Werstiuk et al 32 Bicyclic carbene, containing both α-sulfinyl and α-ester moieties, was registered in the excited triplet state by O'Sullivan et al using nanosecond timeresolved laser flash photolysis. 33 Recently, we found that roomtemperature photolysis of 5-alkylthioethynyl-3,3-dimethyl-3Hpyrazoles led to the generation of previously unknown (4methylpent-3-en-1-ynyl)alkylthiocarbenes, which can be trapped by simple alkenes with formation of corresponding cyclopropanes. 34 This data indicates a high reactivity of these highly unsaturated carbenes, which can be used for synthetic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The α-diazocarbonyl compounds produced by diazo transfer are an important class of versatile synthetic intermediates due to their ability to generate reactive carbenes, [5][6][7] carbenoids, [7][8][9][10][11][12][13][14][15][16][17][18][19][20] ketenes and other heteroanalogous intermediates. [21][22][23][24][25][26] Despite being routinely used in small scale α-diazocarbonyl synthesis, tosyl azide is not suitable for use at larger scales. Tosyl azide has an impact sensitivity of 50 kg·cm, and explosive thermal decomposition can initiate at 120 °C.…”
Section: Introductionmentioning
confidence: 99%
“…α-Diazosulfoxides, like most other α-diazocarbonyl compounds, are exceptionally reactive compounds under transition metal catalysis, photolysis, thermolysis, and microwave irradiation conditions leading to α-oxo sulfine intermediates in a hetero-Wolff rearrangement (Scheme 1) [28][29][30][31]. The utility and synthetic versatility of α-oxo sulfines have been reported and reviewed in the literature [32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%